Resolving the Large Exokuiper Belt of the Hd 126062 Debris Disc and Extended Gas Emission in Its Vicinity - Perez-Marquez, S; Miley, J (EDP Sciences, 2025)
Context. Intermediate mass stars (1–3 M⊙) host some of the brightest and most well-studied debris discs. This stellar class is also the most frequent host of molecular gas in systems with ages beyond typical protoplanetary disc lifetimes and the most likely to host detected giant planets in radial velocity surveys. The debris discs of intermediate mass stars have therefore become a fertile ground for studying disc-planet interactions. Aims. In this work, we present the first ALMA observations towards the A-type star HD 126062, located in Upper Centaurus Lupus/Lower Centaurus Crux, with the aim of characterising the properties of its debris disc. Methods. We probed the thermal continuum emission using observations at 1.3 mm, which were analysed through image reconstruction while employing different visibility weighting regimes in addition to parametric model fitting to the observed visibilities. The observational setup also covers the frequency of the 12CO molecular line, allowing for imaging of gas in the vicinity of the system. Results. We detected the dust continuum emission from an exoKuiper belt around HD 126062. Modelled as a Gaussian ring, the visibilities are consistent with a radial separation of R=2.01−0.05+0.04′′, which is equivalent to ≈270−4+5 au, and a full width half maximum of ΔR=0.71″ ± 0.09, or 95 ± 12 au. The continuum emission appears in an almost face-on configuration with an inclination to the line of sight constrained to be ≤17°.12CO(2–1) emission is detected in the vicinity of the debris disc, with the majority of the emission found external to the exoKuiper belt. Conclusions. The exoKuiper belt characterised here is one of the largest to be detected, and it is consistent with the previous predictions of the distribution of dust in the system based on spectral energy distribution fitting. The morphology and displacement in velocity with respect to the systemic velocity suggest that the gas is not associated with the star and debris disc, and it most likely originates from a diffuse gas cloud in the nearby galaxy. © The Authors 2025.